Análise do gerenciamento de resíduos de equipamentos eletroeletrônicos residenciais em Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Waste electrical and electronic equipment (WEEE) have toxic compounds as well as materials susceptible of reutilization, deserving for instance an especial attention to the extent that there is a growing trend to sell such equipments, and consequently increasing the making of this kind of residues. By means of international and national levels it is possible to identify directives, specific laws, studies and several other proceedings ruling REEE problem. In this study, besides bibliographic survey, it was utilized data collected from actors interviews (customers, recycling and technical support enterprises, environmental control agencies), which turned possible to formulate REE flux, and estimate REEE production in 2020. In Manaus there is still a lack of investigation toward REEE thematic especially linked to post-consumption housing residues and inadequate logistical structure of several modals (aerial, roadway, and fluvial) imperiling the establishment of reverse logistical system. In regard to the estimate production for Manaus in 2020, it was found 0,03 kg/in habitant, computer 0,96 kg/in habitant television set 0,44 kg/in habitant and refrigerator 3,49 kg/in habitant the sum of that equipment totaling 4.92 kg/in habitant. As for REEE logistic practical reverse, we figured out that they are still very timid and actions identified were for the most part at international and national scenario. Results showed absence in Manaus of a system and/or plan of management for REEE post housing consumption, as well as enterprises and population inertia concerning the destination of this kind of residues, i.e. both of them wait for governmental initiative, in this sense REEE turned to donation is sent to sanitary levee together with domiciliary residues.
Keywords: Resíduos de Equipamentos Eletroeletrônicos; Manaus; Logística Reversa; PNRS; Residues of Electro-electronic Equipments; Manaus; Reverse Logistics; PNRS; CIÊNCIAS AGRÁRIAS